2022
DOI: 10.1093/eurheartj/ehac470
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in arterial hypertension

Abstract: There is strong evidence that sex chromosomes and sex hormones influence blood pressure (BP) regulation, distribution of cardiovascular (CV) risk factors and co-morbidities differentially in females and males with essential arterial hypertension. The risk for CV disease increases at a lower BP level in females than in males, suggesting that sex-specific thresholds for diagnosis of hypertension may be reasonable. However, due to paucity of data, in particularly from specifically designed clinical trials, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
84
1
20

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(108 citation statements)
references
References 181 publications
3
84
1
20
Order By: Relevance
“…Large-scale epidemiological studies indicate the presence of visible men-women differences in BP [2,6,8,82,89,90]. At that, these differences were more noticeable in high-income countries and those in Central/Eastern Europe than in the countries of other regions [89].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale epidemiological studies indicate the presence of visible men-women differences in BP [2,6,8,82,89,90]. At that, these differences were more noticeable in high-income countries and those in Central/Eastern Europe than in the countries of other regions [89].…”
Section: Discussionmentioning
confidence: 99%
“…Together with this, an important value in the HTN susceptibility is played by sex hormones, which, firstly, are directly involved in the process regulation of vasoconstriction/vasodilation [90][91][92][93]; secondly, they have a pronounced influence on a number of cardiovascular/HTN risk factors (distribution of adipose tissue in the body, the development of obesity and metabolic syndrome, the formation of obesity-dependent/independent insulin resistance, etc.) [7]; thirdly, they can be significant "modifiers" in the phenotypic manifestation of potential genetic determinants of HTN by modulating various nuclear and extra-nuclear pathways that control the expression of multiple genes, post-translational modifications of protein molecules, various HTN-impact signaling pathways, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Hoste et al found hypertension and liver failure to be risk factors for AKI in hospitalized patients [29]. Both factors are especially prevalent in males and could be other causes for the gender disparities in AKI incidence [30,31]. The direct and indirect influence gender has on the risk of AKI is highly complex and warrants further research to advance gender-specific personalized care and prevention.…”
Section: Gender Disparitiesmentioning
confidence: 99%
“…Unter Diuretika entwickeln Frauen häufiger Elektrolytstörungen (Hyponatriämie und Hypokaliämie) ▶ Tab. 3 Hypertonie-Interventionsstudien mit Auswertung der Ergebnisse, stratifiziert nach Geschlecht (nach Daten aus [31]).…”
Section: Unerwünschte Wirkungenunclassified
“…Männer entwickeln häufiger eine Gicht unter Diuretika und eine sexuelle Dysfunktion, insbesondere bei Betablockern.Kritik an SPRINTDie amerikanische SPRINT-Studie[38] ist zurechtinsbesondere in Europakritisiert worden und hat hier nicht zur Herabsetzung des Zielblutdrucks in den europäischen Leitlinien geführt, im Gegensatz zu den in den USA gültigen. Der Anteil der Frauen in SPRINT war zu gering, um insbesondere bei älteren Frauen den Profit einer intensiven Blutdrucksenkung zu belegen[31,39]. Zudem kommen 2 Subgruppenanalysen zu unterschiedlichen Ergebnissen[40,41]!…”
unclassified